An Empirical Comparison of Seven Populist Attitudes Scales. (June 2020) - Castanho Silva, Bruno; Jungkunz, Sebastian; Helbling, Marc; Littvay, Levente
With the recent upsurge of populism in developed and transition democracies, researchers have started measuring it as an attitude. Several scales have been proposed for this purpose. However, there is little direct comparison between the available alternatives. Scholars who wish to measure populist attitudes have little information available to help select the best scale for their purposes. In this article, we directly compare seven populist attitudes scales from multiple perspectives: conceptual development, questionnaire design, dimensionality, information, cross-national validity, and external validity. We use original survey data collected online from nine countries in Europe and the Americas, with around 250 participants per country, in which all seven batteries of questions were present. Results show that most scales have important methodological and validity limitations in at least one of the dimensions tested, and should not be used for cross-national comparative research. We recommend populist attitudes items that work better at capturing populism, and more generally provide guidelines for researchers who want to compare different scales that supposedly measure the same construct.